Edukasi Kesehatan Melalui Webinar No Kidney, No Life : Upaya Pencegahan Penyakit Ginjal dengan Kontrol Gula Darah - Neshya Ruriana Putri; Maulana Hasymi Hutabarat; Luluk Hermawati; Ekawati Rini Wulansari; Ghea Farmaning Thias Putri; Firda Asma’ul Husna (Jurnal Pengabdian Masyarakat, 2026)
Chronic kidney disease is a global health problem with an increasing prevalence, largely driven by high sugar consumption that contributes to diabetes mellitus as a major risk factor. Community-based health education is essential to raise public awareness of the importance of blood glucose control in maintaining kidney function. This community service activity was conducted in the form of a health webinar entitled “No Kidney, No Life: Keep the Sweetness of Your Life by Controlling Your Blood Sugar,” featuring a speaker specializing in laboratory medicine. The webinar was held online via the Zoom Meeting platform on September 19, 2025, and was attended by participants from diverse backgrounds, including students, lecturers, and healthcare professionals. The activity employed interactive health education methods and a question-and-answer session to encourage active participation. The results demonstrated high participant enthusiasm and improved understanding of the relationship between sugar consumption and the risk of kidney disease, as reflected in active discussions and positive feedback. This activity indicates that online health education can serve as an effective educational medium while strengthening the role of educational institutions in supporting preventive efforts against kidney disease. In the future, similar programs should be developed sustainably to expand their impact in fostering public awareness of kidney health through healthy lifestyle practices.